علاقة الشركة القابضة بالشركات التابعة : دراسة في الآثار المترتبة عليها في القانون الليبي - Mohamed Mohamed M Edhir (Universiti Sains Islam Malaysia, 2024)
The administrative and financial control of the holding company of its subsidiaries requires an integrated legal regulation that shows all the rights and obligations. The regulation of the relationship between the holding company and the subsidiaries does not clarify the extent to which the holding company is responsible for the debts of its subsidiaries. Thus, these are causing the loss of the rights of companies, and third parties. As such, both the expiration and withdrawal of the holding company needs to be organized and detailed. The aim of this study is to study the implicationship between the holding company and the subsidiaries in all aspects of this relationship by studying and analyzing the provisions and devising the effects mentioned in the Libyan law and the Egyptian and Algerian laws as well as evaluating them. Subsequently, the study will aim towards the establishment of an integrated legislative model governing the work of the holding company and subsidiaries. In order to achieve this goal, the researcher followed the comparative and analytical method to analyse the texts of the provisions of the holding company in the Libyan law, and compare them with the texts contained in both the Egyptian and Algerian laws, and knowledge of the position of Islamic jurisprudence on them,and clarify the implications of this relationship. The study concluded that the subsidiary companies,although legally independent, have a separate financial asset. However, this legal independence is only deceptive. The centralised control exercised by the holding company of its subsidiaries empties this independence. Consequently, the subsidiary is no longer independent of the will of the holding company, which leads to the loss of its administrative and financial independence. Most countries lack the legal regulation that shows the liability of the holding company for the debts of its subsidiaries. Therefore,these countries have established the general provisions concerning the holding company and its subsidiaries and left the judiciary to separate the responsibility of the holding company for the debts of its companies. Nevertheless, the effects of the expiration of the holding company on the subsidiary companies is the loss of the association of partnership and control and the disintegration of the grouping of companies as a single body. Moreover, these affect the relationship of the holding company in the subsidiaries and the implications of the award if it was in accordance with the rules of jurisprudence. However, it was not intended to do the work that is prohibited, or corrupt. Due to the lack of legislation targeted study, the researcher creared a legislative model for the work of the holding company and subsidiaries in the public and private sectors.